Comparative analysis of LTE-M/NB-IoT technologies for M2M devices and resource redistribution - Nkaru Chizoba Kingsley; Kadatska, O. (ХНУРЕ, 2025)
In spontaneous connections, the limited bandwidth allocated to M2M devices in LTE-M/NB-IoT networks is expected to be quickly depleted due to the high arrival demand for M2M devices to access the network. To solve the bandwidth limitation problem, bandwidth expansion is used during the period of abnormal events when many M2M devices are connected. The maximum bandwidth limitation and the resource redistribution case are calculated, which results in a significant increase in M2M traffic.
Keywords: comparative analysis; M2M device